Signs of Life : Melbourne International Biennial 1999. - 't Jolle, Sven; Abildgaard, Dorthe; Boers, Waling; Bovier, Lionel; Budney, Jen; Cherix, Christophe; Du, Huang; Eiebakke, Anders; Engberg, Juliana; Flores, Patrick; Fronsacq, Julien; Heise, Henrietta; et al. (Melbourne : City of Melbourne, 1999)
't Jolle, Sven ; Ahtila, Eija-Liisa ; Alÿs, Francis ; Art Orienté Objet ; Asdam, Knut ; Bello, Paola Di ; Birchler, Alexander ; Bird, Terri ; Bonvicini, Monica ; Bourgeois, Louise ; Braeckman, Dirk ; Bush, Stephen ; Cattelan, Maurizio ; Croft, Brenda L. ; Davids, Yael ; Deacon, Destiny ; Dejanov, Plamen ; Dragset, Ingar ; Dunsmore, Amanda ; Elmgreen, Michael ; Farmer, Geoffrey ; Ferreira, Angela ; Frankland, John ; Gligorov, Robert ; Gober, Robert ; Gussin, Graham ; Heger, Swetlana ; Heise, Henrietta ; Hubbard, Teresa ; Ikemura, Leiko ; Van Imschoot, Jan ; Isaeus-Berlin, Meta ; Jakobsen, Jakob ; Jones, Lyndal ; Jouve, Valérie ; Kennedy, Peter ; Kersels, Martin ; Koelewijn, Job ; Krystufek, Elke ; Lange, Andrea ; Li ; Lupini, Mauricio ; MacLeed, Myfanwy ; Maloberti, Marcello ; Marossi, Roberto ; Matteo, Gabriele Di ; McCail, Chad ; Mik, Aernout ; Miyajima, Tatsuo ; Morton, Callum ; Narkevicius, Deimantas ; Neudecker, Mariele ; Niemi-Junkola, Fanni ; Noonan, David ; Norrie, Susan ; OLO ; Ooms, Anne ; Opie, Catherine ; Palma, Miguel ; Parker, Cornelia ; Penalva, João ; Philipsz, Susan ; Piccinini, Patricia ; Rasmussen, Hans Hamid ; Recke, Nikolaj ; Rodland, Torbjorn ; Rondinone, Ugo ; Schneider, Anne ; Shark LeWitt, Vivienne ; Shipsides, Dan ; Smith/Stewart ; Spranzi, Alessandra ; Stucki, Sidney ; Swallow, Ricky ; Tan, Gerardo ; Terada, Ron ; Theis, Bert ; Tropa, Francisco ; Umbaca, Enzo ; Villesen, Gitte ; Wang Jianwei ; West, Franz ; Yanabe, Kenji ; Yanagi Miwa ; Yongbin, Li
CD-Rom zie speciale kast
biog., ind. tent., gr. tent., bibliog. p. 241-246
Engels
Signs of Life : Melbourne International Biennial 1999 : pav. Italië, 14 May - 27 June 1999
boek